On the possibility of automation-induced stagnation - Emanuel Gasteiger; Klaus Prettner (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2017)
We analyze the long-run growth effects of automation in the standard overlap- ping generations framework. We show that, in contrast to other neoclassical models of capital accumulation, automation does not promote growth but induces economic stagnation. The reason is that automation suppresses wages, which are the only source of investment in the overlapping generations framework.
urn:nbn:de:bsz:100-opus-13389
Keywords: J10; J20; O14; O33; O41; 330; automation; robots; investment; stagnation; economic growth; overlapping generations model